2013
DOI: 10.1007/s40263-013-0083-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Injectable Formulations of New-Generation Antipsychotics: A Review from a Clinical Perspective

Abstract: Antipsychotics are the mainstay of the long-term treatment of patients with schizophrenia. In this context, the evidence also supports the effectiveness of long-acting injections (LAIs) or depots of antipsychotics regarding their relapse-preventing properties. When a LAI formulation of risperidone was launched as the first second-generation depot, there was a renaissance of interest in these formulations. In the meantime, olanzapine, paliperidone, and aripiprazole have been approved by regulatory authorities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 92 publications
3
36
0
2
Order By: Relevance
“…Th ese preliminary results are consistent with previous reports indicating the switch from oral to LAI antipsychotic treatment as a safe and eff ective intervention in clinically stable schizophrenic and schizoaff ective patients (Ju et al 2014;Kaplan et al 2013;Lafeuille et al 2013;Rauch and Fleischhacker 2013). Th is seems to be further confi rmed by the almost-complete patients ' adherence to our protocol and by the lack of adjustments of concomitant treatments found in our study.…”
Section: Lai Antipsychotic Treatment From the Outsidesupporting
confidence: 92%
See 1 more Smart Citation
“…Th ese preliminary results are consistent with previous reports indicating the switch from oral to LAI antipsychotic treatment as a safe and eff ective intervention in clinically stable schizophrenic and schizoaff ective patients (Ju et al 2014;Kaplan et al 2013;Lafeuille et al 2013;Rauch and Fleischhacker 2013). Th is seems to be further confi rmed by the almost-complete patients ' adherence to our protocol and by the lack of adjustments of concomitant treatments found in our study.…”
Section: Lai Antipsychotic Treatment From the Outsidesupporting
confidence: 92%
“…Similarly, while the benefi ts of second-generation over fi rst-generation antipsychotics (SGA vs FGA) (Crossley et al 2010;Leucht et al 2013) and of long-acting injectable over oral (LAI vs oral) antipsychotic formulations (Ju et al 2014;Kaplan et al 2013;Lafeuille et al 2013;Rauch and Fleischhacker 2013) in terms of better effi cacy, prevention of relapse, tolerability, and drug kinetics and dynamics have been widely demonstrated, less research have been devoted to the evaluation of the subjective impact of switching antipsychotic administration from oral to LAI (Iyer et al 2013;Kaplan et al 2013;Kirschner et al 2013;Rosa et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Aripiprazole LAI was superior to placebo, and noninferior to oral aripiprazole, in delaying the time to (impending) relapse, as well as in reducing relapse rates. Furthermore, it was suggested that the actual benefit of aripiprazole LAI over oral aripiprazole in clinical practice may be underestimated in the structured setting of a clinical trial [21,40]. Firstly, patients willing and able to participate in a clinical trial are, overall, less likely to be nonadherent to their medication compared with patients generally found in clinical practice.…”
Section: Current Status Of Aripiprazole (Abilify Maintena ò ) In the mentioning
confidence: 99%
“…haloperidol and fluphenazine) and atypical (e.g. risperidone, paliperidone, olanzapine and aripiprazole) agents [20,21]. Besides potentially improving adherence, other advantages of long-acting formulations include relieving patients of the need to take daily medications, the signalling of nonadherence to healthcare workers if patients fail to attend drug administration appointments, and signalling when relapse has occurred despite medication [13,22].…”
Section: Introductionmentioning
confidence: 99%
“…OLAI and oral olanzapine display a very similar profile concerning efficacy and adverse effects [16][17][18][19][20]. However, when using OLAI (compared with the use of other available LAIs) there is a 0.07 % chance of developing a postinjection delirium/sedation syndrome (PDSS) after injection [21], which requires a risk-management plan.…”
mentioning
confidence: 99%